Eksistensi Kantor Wilayah Kementerian Hukum dalam Penyusunan Produk Hukum Daerah - Firra Astria Kristaung; Nurwita Ismail; Arifin Tumuhulawa (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The role and responsibilities of Regional Regulations differ based on the principles and practices stated in the Constitution/UUD and the Regional Government Law. This role is important in ensuring that every regional legal product produced has good substantive and procedural quality. The purpose of this study is to determine and analyze the existence of the Gorontalo Regional Office of the Ministry of Law in improving the quality of regional legal products produced. The method used in this study is an empirical research type, namely legal research based on the reality that researchers obtain in accordance with data in the field. The Gorontalo Regional Office of Law also pays attention to the principle of public participation. In every mentoring process, the regional government involves the community and stakeholders in the preparation of regional regulations. This is an embodiment of the principle of democracy in a state of law, where the law does not only come from above (top-down), but also from below (bottom-up). This strengthens the legitimacy of the law in the eyes of the community and ensures the sustainability of the implementation of these regulations. The existence of the Gorontalo Regional Office of the Ministry of Law plays a central role in efforts to improve the quality of regional legal products. Through the functions of harmonization, consultation, and legal education that are continuously carried out to local governments and stakeholders, the Regional Office contributes greatly to ensuring that every regional regulation produced meets formal legal aspects, but also reflects justice.